DESIGN AND DEVELOPMENT OF WEB-BASED DAILY FINANCIAL RECORDING APPLICATION (CASE STUDY IN YANI JUWITA’S PINK CLINIC) - Lulu Hadisty (Ebiz Prima Nusa, 2023)
Clinic 's Pink is a company engaged in the health sector that serves examinations related to mothers and children. Clinic Pink in running it requires a daily financial recording application that is used to see the progress of total income and expenses. However, the company still uses the conventional system to record these transactions. Things that happened included damaged, lost, dirty documents, made it difficult to recap report data, made it difficult to separate income for services or drugs and there was no information on payment methods. In addition, limited resources also result in less effective reporting to management. Therefore, a web that is more complete and simple so that all recording information can be integrated into one system. The design is carried out by utilizing digitization to make it easier to access, summarize the workflow and minimize errors that occur. Based on the results of tests carried out, the application is in accordance with the desired standard both in the user's point of view and the appearance of the application. Thus the results of this final project can be used as an alternative application for clinics in carrying out financial records.